Featured Article: Characterization of cultured multipotent zebrafish neural crest cells. (February 2014) - Kinikoglu, Beste; Kong, Yawei; Liao, Eric C
The neural crest is a unique cell population associated with vertebrate evolution. Neural crest cells (NCCs) are characterized by their multipotent and migratory potentials. While zebrafish is a powerful genetic model organism, the isolation and culture of zebrafish NCCs would provide a useful adjunct to fully interrogate the genetic networks that regulate NCC development. Here we report for the first time the isolation, in vitro culture, and characterization of NCCs from zebrafish embryos. NCCs were isolated from transgenic sox10:egfp embryos using fluorescence activated cell sorting and cultured in complex culture medium without feeder layers. NCC multilineage differentiation was determined by immunocytochemistry and real-time qPCR, cell migration was assessed by wound healing assay, and the proliferation index was calculated by immunostaining against the mitosis marker phospho-histone H3. Cultured NCCs expressed major neural crest lineage markers such as sox10, sox9a, hnk1, p75, dlx2a, and pax3, and the pluripotency markers c-myc and klf4 . We showed that the cultured NCCs can be differentiated into multiple neural crest lineages, contributing to neurons, glial cells, smooth muscle cells, melanocytes, and chondrocytes. We applied the NCC in vitro model to study the effect of retinoic acid on NCC development. We showed that retinoic acid had a profound effect on NCC morphology and differentiation, significantly inhibited proliferation and enhanced cell migration. The availability of high numbers of NCCs and reproducible functional assays offers new opportunities for mechanistic studies of neural crest development, in genetic and chemical biology applications.